(untitled) (المجلة الدولية للبحوث العلمية, 2025)
Air pollution refers to the release of various gases, solid particles, and dispersed liquids into the atmosphere at rates that exceed the environment’s ability to disperse, absorb, or neutralize them. In this study, a simulation program was developed using MATLAB to calculate the real-time concentrations of pollutants in Baghdad city, including PM2.5, CO, SO₂, NO₂, and O₃. Air pollution levels were monitored based on real-time air quality indicators. The results showed that the air quality in Baghdad is classified as very unhealthy for most months of the year, and "unhealthy" for sensitive groups due to exposure to fine particles and dust. A key feature of this work is the ability to generate simulation data that closely matches actual data obtained from the Air Quality Map, relying on radar monitoring above the U.S. Embassy in Baghdad. The results highlight the urgent need for effective measures to reduce pollution levels and improve air quality in the city.